Researching music in Slovenia - Nagode, Aleš (Muzikološki zbornik, 2020)
The article observes distortions of the historiographical narrative about the musical culture of Slovenia in the past, caused by specific circumstances of the formation of the Slovenian nation and the dominance of nationalism. It also outlines the strategies applied by Slovenian musicology since the second half of the twentieth century to escape the grip of nationalistic ideology.
Keywords: history; methodology; metodologija; musicology; muzikologija; nacionalno gibanje; nationalism; Slovene music; Slovenia; Slovenija; slovenska glasba; zgodovina